Fixed switching frequency control using trapezoidal current mode to achieve ZVS in three-level DC-DC converters - Yao, Zhigang (2025)
Generally, the variable switching frequency method is used to operate power converters in triangular current mode (TCM) or near critical conduction mode (CRM) to achieve zero-voltage switching (ZVS). However, this approach faces significant challenges: high peak inductor current, and complex controller design due to varied digital delays in variable frequency operation. To address these challenges, this article proposes a novel fixed switching frequency control method using trapezoidal current mode (TZCM) to mitigate the inductor peak current while realizing ZVS for three-level dc-dc converters. A relationship between the average inductor current and the two duty cycles is modeled to determine the appropriate trapezoidal current shape in near-CRM. By simultaneously adjusting two duty cycles and alternating them within each switching period, ZVS is successfully achieved at a fixed switching frequency. Compared with traditional methods, the proposed method not only improves the converter efficiency, especially at light loads, but also pioneers a fixed frequency scheme for achieving ZVS applicable to all three-level dc-dc converters. The proposed control is experimentally validated on a 2 kW prototype, achieving an efficiency of 99.12%.